A TRANSLATION ANALYSIS OF DELETION STRATEGY IN SUBTITLING OF THE FILM ENTITLED A CINDERELLA STORY - MASLAHAH, FRIDA ALFANI (2010)
The objectives of this study are to describe: (1) the linguistic form deletion strategy in subtitling, (2) the reasons of the subtitler in using deletion strategy, (3) the number of subtitling which is equivalent and non equivalent. The writer wants to analyze one of the strategies that subtitler uses in subtitling based on translation rules. The writer employs descriptive qualitative method. By this method, the writer uses the subtitling A Cinderella Story film as the data source, and the data are Indonesian simple sentence. As the comparison, there are also data from the manuscript in English. The technique of the data collection is documentation tecnique. The technique of analysis the data is comparing technique. The results of this research show that: first, there are 4 linguistic forms of deletion which were used by the subtitler in subtitling. From 60 data, the writer finds 73 cases because 13 data contains more than one. There are 62 or 84,94% case belongs to words, 3 or 4,1% case belongs to phrase, 1 or 1,37% case belongs to clause, 7 or 9,59% case belongs to sentence. Second, from 60 data, there are 9 or 15% data belongs to reason general aim, 7 or 11,67% data belongs to reason duration, 44 or 73,34% data belongs to reason readability. Third, from 60 data, there are 56 or 93,33% belong to equivalent 4 or 6,67% data belong to non equivalent.